Lyme borreliosis in pregnancy and associations with parent and offspring health outcomes: An international cross-sectional survey - Leavey, Katherine; MacKenzie, Rachel K.; Faber, Sue; Lloyd, Vett K.; Mao, Charlotte; Wills, Melanie K. B.; Boucoiran, Isabelle; Cates, Elizabeth C.; Omar, Abeer; Marquez, Olivia; Darling, Elizabeth K. (Frontiers in Medicine, 2022)
Background Lyme disease (LD) is a complex tick-borne pathology caused by Borrelia burgdorferi sensu lato bacteria. Currently, there are limited data regarding the health outcomes of people infected during pregnancy, the potential for perinatal transmission to their fetus, and the long-term effects on these children. Therefore, the primary objective of this survey study was to investigate the impact of LD in pregnancy on both the parent and their offspring. Methods A seven-section survey was developed and administered in REDCap. Although recruitment was primarily through LD-focused organizations, participation was open to anyone over the age of 18 who had been pregnant. Participant health/symptoms were compared across those with “Diagnosed LD,” “Suspected LD,” or “No LD” at any time in their lives. The timing of LD events in the participants’ histories (tick bite, diagnosis, treatment start, etc.) were then utilized to classify the participants’ pregnancies into one of five groups: “Probable Treated LD,” “Probable Untreated LD,” “Possible Untreated LD,” “No Evidence of LD,” and “Unclear.” Results A total of 691 eligible people participated in the survey, of whom 65% had Diagnosed LD, 6% had Suspected LD, and 29% had No LD ever. Both the Diagnosed LD and Suspected LD groups indicated a high symptom burden (p < 0.01). Unfortunately, direct testing of fetal/newborn tissues for Borrelia burgdorferi only occurred following 3% of pregnancies at risk of transmission; positive/equivocal results were obtained in 14% of these cases. Pregnancies with No Evidence of LD experienced the fewest complications (p < 0.01) and were most likely to result in a live birth (p = 0.01) and limited short- and long-term offspring pathologies (p < 0.01). Within the LD-affected pregnancy groups, obtaining treatment did not decrease complications for the parent themselves but did ameliorate neonatal health status, with reduced rates of rashes, hypotonia, and respiratory distress (all p < 0.01). The impact of parent LD treatment on longer-term child outcomes was less clear. Conclusion Overall, this pioneering survey represents significant progress toward understanding the effects of LD on pregnancy and child health. A large prospective study of pregnant people with LD, combining consistent diagnostic testing, exhaustive assessment of fetal/newborn samples, and long-term offspring follow-up, is warranted.